The Social Value of Health Insurance Results from Ghana - Garcia-Mandico, Silvia (World Bank, Washington, DC, 2019)
This paper uses the roll-out of the national health insurance in Ghana to assess the cushioning effect of coverage on the financial consequences of health shocks and resulting changes in coping behaviors. The analysis finds a strong reduction in medical expenditures, preventing households from cutting non-food consumption and causing a decrease in the volume of received remittances as well as the labor supply of healthy adult household members. Moreover, the paper presents evidence that the insurance scheme reduced the likelihood that households experiencing a health shock pulled their children out of school to put them to work. Avoidance of such costly coping mechanisms is potentially an important part of the social value of formal health insurance.